MTEACOGNITIVE APPROACH – A PRACTICAL APPROACH FOR TEACHING COMPUTERS - Sood, Payal; Parmar, Tripta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper deals with the concept of Meta Cognitive solutions for teaching computer science. Most beginners at school level face many challenges while learning computers. The paper deals with use of metacognitive interventions for dealing with their challenges like awareness and understanding the metacognitive interventions. The paper also includes a qualitative case study of use of metacognitive interventions by computer teachers. The difference which metacognition makes in the classroom environment has been established in the case study. The improvement in the attitude of teachers as well as that of the students for a better teaching and learning environment has been established in the paper. The teaching of computer science can be made more effective by creating awareness and understanding of metacognitive approach among computer teachers and it can make teaching more entertaining also.